Training and Education for Ventilator use and Operations among Saudi Healthcare Workers: Systematic Review - Mohammed Abdu Rajhi; Fatimah Ahmed Khormi; Fatim Mohammed Masmali; Amal Ali Najmi; Ameera Hamoud Zoqail; Amal Ahmed Khormi; Sarah Abdullah Alamoudi; Yaqoub Abdullah Daghas; Sarah Hassan Maqbul; Sharifah Ahmed Khormi (Migration Letters, 2023)
Background: Ensuring that healthcare workers receive proper training and education in ventilator use and operations is of utmost importance. By doing this, we have the opportunity to significantly improve patient outcomes and strengthen the resilience of our healthcare system. Aim: The main objective of this study is to thoroughly examine and evaluate the crucial factors that play a significant role in the triumph of training and education initiatives centered on the utilization of ventilators by healthcare professionals in Saudi Arabia. Through examining these components, we can gain a deeper comprehension of how these programs ultimately contribute to enhanced patient outcomes and strengthen the overall resilience of the healthcare system.. Method: The study population comprises healthcare workers in Saudi Arabia involved in ventilator use and operations. Comprehensive training and education programs are examined, and their effectiveness is compared with other training approaches or non-trained healthcare workers. Patient outcomes, healthcare system resilience, and healthcare worker proficiency in ventilator use are assessed over the period from 2019 to 2023 with n = 15. Results: The findings highlight that comprehensive, standardized training programs significantly enhance healthcare worker proficiency in ventilator use. These programs contribute to improved patient outcomes, including reduced mortality rates and complications. Furthermore, healthcare system resilience is strengthened as trained workers demonstrate better preparedness and response during healthcare crises. Conclusion: Effective training and education programs for ventilator use among Saudi healthcare workers are essential for improving patient care and enhancing healthcare system resilience. Continuous investment in education and competence assessment is recommended to meet evolving healthcare demands and ensure preparedness for critical situations.